Designing Gold Nanoparticle-Ensembles as Surface Enhanced Raman Scattering Tags inside Human Retinal Cells - Sanda Boca; Dumitrita Rugina; Adela Pintea; Nicolae Leopold; Simion Astilean (Journal of Nanotechnology)
Apart from the traditional development of surface-enhanced raman scattering (SERS) substrates for ultrasensitive spectroscopic analysis, an increasing interest is given nowadays to the design of the so-called SERS nanotags which integrate multiple SERS applications into single plasmonic nanoparticles. The fabrication of SERS tags is still a challenging task due to the complicated fabrication process. Typically, SERS tags are hybrid nanoconstructs consisting in a unique plasmonic nanoobject encoded with specific reporter molecules and enveloped in a protective shell that provides both biocompatibility and targeting function. Herein, we produce effective SERS tags consisting in small aggregates of gold nanoparticles (mainly dimers and trimers) which are captured from solution and then transferred into cells to perform as individual plasmonic nanostructures. Actually the small aggregates formed under controlled conditions are stabilized in solution by interlocking into a polymeric envelope made of thiol-modified poly(ethylene) glycol (PEG-SH). No further encoding operation is necessary in our case since part of ascorbic acid used as reducing agent remains attached in the interparticle junctions, providing persistent and strong SERS signal when the fabricated tags are internalized by human retinal cells. Our studies demonstrate a promising potential of new SERS-active nanoparticles to serve as effective reporters for biomedical tracing and imaging.